Modality and Self-Positioning in Instagram Posts: A Semantic–Pragmatic Analysis of Interpersonal Meaning in Digital Personal Branding - Lilis Adelika; Firda Harlidayana; Zara Mahfuza; Nur zakia Khoiron; Vika Sihombing; Meisuri Meisuri (Pusat riset dan Inovasi Nasional, 2026)
This study examines the use of modality in Instagram posts to express interpersonal meaning and self-positioning in the context of digital personal branding. Based on Palmer’s (2001) theory, this study aims to identify the types of modality and their functions in conveying speakers’ attitudes, beliefs, obligations, and abilities. The data consist of 30 modal expressions analyzed using a qualitative semantic–pragmatic approach. The analysis reveals three types of modality: deontic, epistemic, and dynamic, with deontic modality as the most dominant (11 data/36.67%), followed by epistemic (10 data/33.33%) and dynamic (9 data/30%). Deontic modality is used to express obligation and social norms, for example through the use of harus and tidak boleh; epistemic modality expresses belief and degrees of certainty, such as mungkin and pasti; while dynamic modality indicates ability and intention, such as ingin and mau. These findings demonstrate that modality plays an important role in constructing interpersonal meaning and speaker positioning in digital discourse, particularly on Instagram.